Ten Commandments of Faith-Based Recruitment - Lefler, Leanne L. (Research in gerontological nursing, 2009)
Recruitment of older adults for clinical research, especially racial/ethnic minorities, is challenging at best. This article reports the author's experience and reviews current literature regarding faith-based methods to recruit older Black and White women for research. Her work and the literature review suggest 10 major recommendations for faith-based recruitment. Recommendations include: Select only faith institutions with religious leaders who actively advocate and collaborate; select key advisors or “insiders” to facilitate and customize the study; use culturally appropriate and age-sensitive recruitment and study materials; use faith institution facilities and promote access; use incentives; increase “face time”; use existing faith groups to encourage peer support; make it a social event and make it fun; provide personal benefit to participation; and customize spirituality. Involvement with faith institutions may be essential to reach groups who have been underrepresented in research.